2019
DOI: 10.1111/acem.13823
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Financial Incentives on Patient Decisions to Undergo Low‐value Head Computed Tomography Scans

Abstract: After reading the article, participants should be able to discuss the influence of financial incentives, accompanied with information regarding risk and benefit, on patient preferences for diagnostic testing. Activity Disclosures This activity received no commercial support. CME Editor Corey Heitz discloses no relevant financial relationships. This activity underwent peer review in line with standards of editorial integrity and publication ethics. Conflicts of interest have been identified and resolved in acco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 14 publications
(20 reference statements)
1
3
0
Order By: Relevance
“…Additionally, the results of our current study were congruent with our more recent study that analyzed the effect of test benefit, test risk, and financial incentive on patient preference for low-value diagnostic testing with CT head in a minor TBI scenario. 6 This supports that the relationship between these variables may be observed across multiple clinical situations.…”
Section: Discussionsupporting
confidence: 71%
See 3 more Smart Citations
“…Additionally, the results of our current study were congruent with our more recent study that analyzed the effect of test benefit, test risk, and financial incentive on patient preference for low-value diagnostic testing with CT head in a minor TBI scenario. 6 This supports that the relationship between these variables may be observed across multiple clinical situations.…”
Section: Discussionsupporting
confidence: 71%
“…7, 9 A subsequent study focused solely on patient preferences for CT head in minor TBI showed that a financial incentive for patients to forego low-value diagnostic testing also significantly reduced patient preference for this test. 6 While the influence of test benefit and risk on patient decision-making was of mixed statistical significance in our original work, these variables both achieved statistical significance in our CT head/minor TBI study. 6, 9…”
Section: Introductionmentioning
confidence: 73%
See 2 more Smart Citations